Valor económico del volumen maderable y del secuestro de CO2 de un bosque de colina baja del predio privado El Limón, distrito de Jenaro Herrera, Loreto. 2022 - Fernandez Panduro, Angela (2024)
This study compared the CO2 sequestration service and economic values of timber volume of commercial forest species in the low hill forest of Loreto, Jenaro Herrera district. Data from the forest census of the private property El Limón were evaluated. According to the results, the timber has a commercial value of 585,79 USD/ha. The three species with the highest value are Macrolobium angustifolium (234.47 USD/ha), Allantoma decandra (103,61 USD/ha) and Ormosia macrocalyx (90,36 USD/ha). CO2 sequestration has an economic value of 3464,05 USD/ha. The species with the highest economic value are Macrolobium angustifolium (1014,86 USD/ha), Allantoma decandra (781.58 USD/ha) and Ormosia macrocalyx (391,13 USD/ha). The Chi-square test resulted in a p-value = 0,002 lower than α = 0,05, rejecting the null hypothesis and supporting the alternative hypothesis that there is a significant difference between the means of the economic value of timber volume and the economic value of CO2 sequestration in lowland coppices.